Impact of Applying Agile Practices to Bioinformatics Environment (المجلة الدولية للعلوم التربوية والآداب, 2023)
The bioinformatics software development industry represents one of the fastest-growing fields. As a result of the lack of software engineering practices in the development and the complex nature of bioinformatics software development, there is a strong need for more agility in dealing with these challenges. The agile methods represent good development practices that rely on strong collaboration and automation to develop high-quality software within time and budget constraints through several iterations. This paper adopts agile principles, especially extreme programming (XP) practices to solve the common challenges that face the developers of bioinformatics software. The proposed agile practices can be used to facilitate and enhance the development processes which may increase the possibility of its success.